Responsivity optimization of a MQW SOI-based lateral PIN photodiode using Taguchi's L27 orthogonal array - Menon P.S.; Tasirin S.K.; Ahmad I.; Abdullah S.F.; Apte P.R. (2023)
Silicon-on-insulator (SOI)-based lateral PIN photodiodes using SiGe/Si multilayer quantum wells (MQW) are suitable for applications in the near-infrared range both for sensing and optical fiber communication application. The objective of this paper is to optimize the process parameters for such a device using Taguchi's L27 orthogonal array. Five device process parameters and two device noise factors were identified to make the virtual device design insensitive to variation in the selected fabrication parameters. The results obtained for responsivity after the optimization approach was 0.33 A/W for the optimized device with intrinsic region length of 6 ?m, photo-absorption layer thickness of 0.505 ?m, incident optical power of 0.5 mW/cm2, bias voltage of 3.5 V and SOI layer thickness of 0.5 ?m. The percentage of improvement for the device's responsivity is 27% as compared to the previous work. 2013 IEEE.